Intranasally delivered mesenchymal stromal cells decrease glial inflammation early in prion disease - Hay, Arielle J. D.; Latham, Amanda S.; Mumford, Genova; Hines, Amelia D.; Risen, Sydney; Gordon, Elizabeth; Siebenaler, Connor; Gilberto, Vincenzo S.; Zabel, Mark D.; Moreno, Julie A. (Frontiers in Neuroscience, 2023)
Mesenchymal stromal cells (MSCs) are an intriguing avenue for the treatment of neurological disorders due to their ability to migrate to sites of neuroinflammation and respond to paracrine signaling in those sites by secreting cytokines, growth factors, and other neuromodulators. We potentiated this ability by stimulating MSCs with inflammatory molecules, improving their migratory and secretory properties. We investigated the use of intranasally delivered adipose-derived MSCs (AdMSCs) in combating prion disease in a mouse model. Prion disease is a rare, lethal neurodegenerative disease that results from the misfolding and aggregation of the prion protein. Early signs of this disease include neuroinflammation, activation of microglia, and development of reactive astrocytes. Later stages of disease include development of vacuoles, neuronal loss, abundant aggregated prions, and astrogliosis. We demonstrate the ability of AdMSCs to upregulate anti-inflammatory genes and growth factors when stimulated with tumor necrosis factor alpha (TNFα) or prion-infected brain homogenates. We stimulated AdMSCs with TNFα and performed biweekly intranasal deliveries of AdMSCs on mice that had been intracranially inoculated with mouse-adapted prions. At early stages in disease, animals treated with AdMSCs showed decreased vacuolization throughout the brain. Expression of genes associated with Nuclear Factor-kappa B (NF-κB) and Nod-Like Receptor family pyrin domain containing 3 (NLRP3) inflammasome signaling were decreased in the hippocampus. AdMSC treatment promoted a quiescent state in hippocampal microglia by inducing changes in both number and morphology. Animals that received AdMSCs showed a decrease in both overall and reactive astrocyte number, and morphological changes indicative of homeostatic astrocytes. Although this treatment did not prolong survival or rescue neurons, it demonstrates the benefits of MSCs in combatting neuroinflammation and astrogliosis.